2023
DOI: 10.3390/s23031338
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Molecular Cell-Based Sensor to Detect Ligands of PPARs: An Optimized Tool for Drug Discovery in Cyanobacteria

Abstract: Cyanobacteria produce a wealth of secondary metabolites. Since these organisms attach fatty acids into molecules in unprecedented ways, cyanobacteria can serve as a novel source for bioactive compounds acting as ligands for Peroxisome Proliferator-Activated Receptors (PPAR). PPARs (PPARα, PPARβ/δ and PPARγ) are ligand-activated nuclear receptors, involved in the regulation of various metabolic and cellular processes, thus serving as potential drug targets for a variety of pathologies. Yet, given that PPARs’ ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…According to the methods in Ref. [32] and Ref. [33], the limit of quantitation (LOQ) is calculated to be about 287 fg/mL.…”
Section: Measurement Of T Gondii Mabmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the methods in Ref. [32] and Ref. [33], the limit of quantitation (LOQ) is calculated to be about 287 fg/mL.…”
Section: Measurement Of T Gondii Mabmentioning
confidence: 99%
“…According to the methods in Refs. [32,33], the limit of quantitation (LOQ) is calculated to be about 287 fg/mL. It is concluded that the biosensor has extremely low LOD and can be used to detect biomolecules with lower concentration.…”
Section: Measurement Of T Gondii Mabmentioning
confidence: 99%
“…A biosensor is an analytical device that contains a biorecognition element, such as antibodies, enzymes, nucleic acids, and aptamers, as well as a transducer that converts the recognition element into a measurable signal using optical, electrochemical, thermometric, or piezoelectric technology [134,135]. Biosensors are being used in the discovery of drugs and bioactive compounds [135,136]. Páscoa and colleagues (2023) developed a novel wholecell biosensor that incorporated reporter genes for signal intensity and stability, a promoter to modulate Fluc expression, and assay multiplexing to improve efficiency and output.…”
Section: Biosensorsmentioning
confidence: 99%
“…The sensor's selectivity was analyzed using clotrimazole and validated by recognizing fragments of cyanobacterial extracts possessing peroxisome proliferator-activated receptors (PPARs) agonist properties. Multiplex and uniplex screening assays were conducted to determine which PPARs the bioactive extracts were targeting [136].…”
Section: Biosensorsmentioning
confidence: 99%